TINJAUAN KRITIS TERHADAP ISTILAH METODE CAMPURAN (MIXED METHOD) DALAM RISET SOSIAL - Senjaya, Aan Juhana (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2018)
The study of mixed methods in research methodology has become a 'trend' or a trend back after not appearing for several periods. Emerging issues about mixed methods are usually surrounded by definitions, paradigms, and methodologies. Researchers when writing about Mixed Methods raises issues around design, sampling, analysis, and reporting that require skills, cost, and time to research with mixed methods. This paper aims to conduct a critical study of the term mixed methods (Mixed Methods) so it can be more clear what is meant by mixed methods. Hopefully, novice researchers who are interested in doing research do not